Pendekatan Mengurangkan Pembaziran Sisa Bahan Binaan Di Tapak Bina di Malaysia - Amin Zawawi, Nur Iffa Izwani; Seow, Ta Wee; Sarpin, Norliana; Masrom, Md Asrul Nasid (Research in Management of Technology and Business, 2022)
The construction industry is one of the sectors that contributes to economic development. Nevertheless, material waste has been recognized as a common cause of construction waste generation. If, the contractor uses the correct method in dealing with construction waste will be able to reduce the quantity of construction waste generated. This study was conducted to discuss the main causes of construction waste at construction sites, identify the effects of waste of building materials resulting from construction activities as well as study strategies to minimize construction waste used in construction projects. The respondents involved in this study consisted of G7 contractors involved in the construction industry in Penang. Data collection used in this study is a quantitative method through the distribution of questionnaires to obtain primary data, while secondary data is obtained through the reading of reference materials and previous studies. The results of the study found that some of the main causes of waste of building materials are from the aspects of design, personnel, management, procurement, site conditions, handling and external factors. Next, there are several effects from the waste of building materials, namely environmental pollution, increased construction costs, the surrounding population and construction workers. In addition, some of the methods used by contractors to reduce construction material waste at construction sites are through systematic waste management. In conclusion, this study will help in identifying the main causes, effects of waste of building materials and effective methods in addressing the problem of waste of building materials in Malaysia and indirectly improve the quality of construction in the country.